Kegiatan Edukasi Kesehatan Dan Skrining Komposisi Tubuh Dengan Bioelectrical Impedance Analysis Dalam Upaya Pencegahan Obesitas Pada Usia Produktif - Santoso, Alexander Halim; Destra, Edwin; Edbert, Bruce; Gaofman, Brian Albert (Journal of Community Service and Society Empowerment, 2025)
Obesity during productive age significantly increases the risk of various metabolic complications, including diabetes, hypertension, and cardiovascular diseases. Body composition assessment, particularly through Bioelectrical Impedance Analysis (BIA), plays a crucial role in early detection and provides accurate measurement of fat and muscle distribution. BIA enables the identification of body fat percentage and muscle mass, which are key indicators in evaluating health risks and planning appropriate lifestyle interventions. This community health activity employed the Plan–Do–Check–Act (PDCA) approach, focusing on health education and body composition screening using BIA for early obesity detection. A total of 40 participants of productive age groups were involved in this initiative. The average body fat percentage was 26.88%, and the average muscle mass was 25.44%, reflecting a notable risk of obesity in this population.  Health education combined with BIA-based screening has proven effective in raising awareness and promoting early identification of obesity-related risks. Through BIA, participants gained a better understanding of their body composition, which motivated positive lifestyle changes. Regular monitoring of body composition is recommended to help reduce obesity prevalence among productive age groups and to enhance community health and quality of life.